Company Asset Management Information System (Case Study: Branch Office Bpjs Ketenakerjaan, Bogor) - Sandra Jamu Kuryanti; Siti Nur Khasanah; Cep Adiwihardja (Institute of Computer Science (IOCS), 2022)
Technology helps every job and solves problems quickly and efficiently. BPJS Employment Bogor is one of the companies that uses technology to support every work activity. BPJS Employment is a public program that provides protection for workers to overcome certain socio-economic risks and its implementation uses a social insurance mechanism. The research method used by the author is the waterfall model research method, which is often called the linear sequential model or classic life flow. The waterfall model provides a systematic as well as sequential approach to software development, starting with the specification of user requirements and then continuing through the stages of planning, modeling, construction, and handing over the system to customers / users. The recording of borrowing and retrieval of goods, and stock of goods at BPJS Ketenagakerjaan Bogor still uses a ledger, making it possible for data errors, inaccurate data, and data loss to occur.